PENDIDIKAN MORAL AISYAH R.A DALAM BUKU SULAIMAN AN-NADAWI - Siswanto Siswanto; Nirna Lensi; Ifnaldi Nurmal; Eli Susanti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
The purpose of this study is to explain how the concept of moral education contained in Sulaiman An-Nadawi's book. This research is motivated by the need for a solution to overcome the negative impact on the moral field, which currently requires a real person as an example in implementing a moral life. This research is a library research (library research). the main data source is Sulaiman An-Nadawi's book about Aisyah as a Muslim Ummah. The type of data collection in this research is through reading, describing, and reviewing the contents of the book that is being researched or used as a research source, then the type of approach used is content analysis. Sulaiman An-Nadawiini include: (1) The concept of moral education related to God (2) The concept of moral education related to oneself. (3) The concept of moral education related to fellow human beings.